The Effectiveness of Translation Competence in Radio Gotel Yola, Adamawa State, Nigeria. - Baba, Mustapha Abdulhamid; Bappayo, Abubakar; Halilu, Shehu (NIU Journal of Humanities, 2018)
The study was on effectiveness of translation competence in radio gotel Yola, Adamawa state, Nigeria. The objective of the study was to determine the level of effectiveness of language translation at Gotel Radio station in Yola, Adamawa state, Nigeria. The target population was 134 participants while the sample size was computed to 100 respondents using sloven’s formula. The participant included the staff of the Radio Gotel Yola, and listeners of Radio Gotel programs and the main research instrument was questionnaire. The study examined the level of effectiveness of language translation at Gotel radio station in Yola, Adamawa state, that majority of the respondents agreed that translation requires experience and good mastery of the subject matter, that socio-cultural and linguistic background is necessary for good translation. The study concluded that to ensure effective translation, there is need to keep updating the knowledge, skills and competences of the translators. The following recommendations were made: There is need to emphasize proper training and effective training methods for language translators, the Gotel radio should maintain constant interaction and seeking feedback from its listeners in order to gauge whether its program translations meets the expectations of the listeners, lastly the translator should be a native speaker of the language he/she is translating in order to deeply understand the grammar and vocabulary of the language.